Marginalized forest peoples’ perceptions of the legitimacy of governance: an exploration - Colfer, C.J.P. (2011)
Two issues prompted this review: Global concerns to decentralize and democratize will require more effective involvement of now-marginalized people; and addressing global problems (climate change, poverty, forests, and biodiversity loss) will pragmatically require their involvement. This exploratory review examined how marginalized groups in tropical forests have perceived the legitimacy of their forest-related governance. These perceptions are examined within the contexts of gender, age, ethnicity, and occupation. Important mechanisms by which people dealt with their marginalization are also addressed. These issues take on special urgency within the context of the recent global, forest-related climate change discourse.